Estudo do avanço de injeção de biodiesel em um motor dual de ignição por compressão utilizando gás natural e biodiesel - Rocha, Márcio Andrade (2021)
The present work aims to study the advance of biodiesel injection in a dual-fuel engine of the ignition per compression using natural gas and Diesel / biodiesel. The determination of the ideal injection point of Diesel / biodiesel tends to provide complete combustion of the Diesel / biodiesel / CNG mixture in order to maintain the power and torque of the engine originally specified by the manufacturer with exclusive use of Diesel/biodiesel, without generating problems like knock, increase of pollutants released to the environment, decrease of autonomy and increase of costs. A piezoelectric vibration sensor, of the automotive detonation sensor type used on commercially available, low cost flex engine vehicles, was coupled to the MWM 4.07 TCE Diesel engine block. The signals it emitted together with the nozzle opening signal were captured and conditioned in an electronic circuit made to determine the ignition delay. The code elaboration for the electronic circuit was validated by comparing it with the values obtained by oscilloscope. In order to vary the injection advance, was used a Tury Model T30 advance variator used in vehicles equipped with a vehicle natural gas (VNG) system. For the analysis of the obtained results, graphs and tables containing information on ignition delays and variations in the advance using VNG injection and diesel / biodiesel mixtures in three proportions B10, B20 and B50 were prepared. A study of the gases emitted from the information captured by an “Optima 7” gas analyzer installed in the engine exhaust was also developed. Results obtained showed that the use of Diesel / biodiesel / CNG mixture provided: increased Ignition delay; the advance of the fuel injection increased the Ignition delay even more, thus necessitating an advance delay; increase in some emission gases were verified and evaluated as resulting from the use of rich mixtures and or incomplete combustion.